9(2x-4)=3(6x+8)

Simple and best practice solution for 9(2x-4)=3(6x+8) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 9(2x-4)=3(6x+8) equation:


Simplifying
9(2x + -4) = 3(6x + 8)

Reorder the terms:
9(-4 + 2x) = 3(6x + 8)
(-4 * 9 + 2x * 9) = 3(6x + 8)
(-36 + 18x) = 3(6x + 8)

Reorder the terms:
-36 + 18x = 3(8 + 6x)
-36 + 18x = (8 * 3 + 6x * 3)
-36 + 18x = (24 + 18x)

Add '-18x' to each side of the equation.
-36 + 18x + -18x = 24 + 18x + -18x

Combine like terms: 18x + -18x = 0
-36 + 0 = 24 + 18x + -18x
-36 = 24 + 18x + -18x

Combine like terms: 18x + -18x = 0
-36 = 24 + 0
-36 = 24

Solving
-36 = 24

Couldn't find a variable to solve for.

This equation is invalid, the left and right sides are not equal, therefore there is no solution.

See similar equations:

| 8x+2=3x+13 | | -29=-7y-9y | | 36m^2-49/25 | | 14=24 | | 5+9t-2=9t+17-7t | | 9d+5-2d=20 | | x/6=42 | | 24=-2(6a-7) | | 3(x-0.8)=4x-4 | | 3x-21-7x+20= | | 1+2/x+5/x^2=0 | | 1/2+9/x=5/4 | | 10-2p=4q | | 12-3p=q | | 3x+16x=95 | | 7-2(1-3s)=35 | | -21+[-14+(-13)]= | | 15-p=q | | 4(4+2x)=7(x-2) | | y=20-10 | | -2p-2(4-4p)=4(p-4)-18 | | z/4=-10 | | m-1/2=-11/12+11/6m | | 36m^2-25/4 | | -23-8c=7(4c+9) | | 7r=-14 | | 3(2+x)=14+x | | 2x+3=55x | | 8x-25=-33+9x | | 11x+(-12y)+(-15x)+9y= | | 2x-1y=-30 | | Q=75-p |

Equations solver categories